Hybrid pattern-matching algorithm based on BM-KMP algorithm - Hou Xian-feng; Yan Yu-bao; Xia Lu (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
Reading and reference many books and articles, and then analyze and study the KMP algorithm, BM algorithm and a variety of improved algorithms. Summarizes various of the advantages and disadvantages of the pattern matching algorithms and in-depth study the advantages of the algorithms. And on this basis, a new algorithm - KMPBS algorithm is introduced. The algorithm refers to BM algorithm, KMP algorithm and the thinking of improved algorithms. Utilize the last character of the string, the next character and the method to compare from side to side, and then advance a new hybrid pattern matching algorithm. And it adjusted the comparison direction and the order of the comparison to make the maximum moving distance of each time to reduce the pattern matching time. The algorithm reduces the comparison number and greatly reduces the moving number of the pattern and improve the matching efficiency. This algorithm achieved a better result and it works well.